The Importance of Community: How Modular Organization of Social Networks Affects their Collective Dynamics. (June 2014) - Sinha, Sitabhra
Complex networks, comprising tens to thousands of nodes are ubiquitous in society, ranging from acquaintance networks—which are of interest in sociology— to networks of interactions between companies and financial institutions—which are of interest in economics. A large number of such systems exhibit structural patterns that appear to be universal. One such organizational feature seen in many networks is modularity, where the network is divided into several connected clusters ('communities') with the connection density in each cluster being significantly higher than that for the entire network. Modularity can often be also hierarchical, appearing at several different scales. Recent advances in reconstructing networks from empirical data have shown that modularity is ubiquitous. In this article we explore the role of modularity in organizing the collective dynamics of social networks. The lessons of this analysis may have important implications for understanding the process of consensus formation through individuals affecting the opinions of their neighbours via interactions through the links of the social network.